1990
DOI: 10.1021/bi00457a019
|View full text |Cite
|
Sign up to set email alerts
|

Structure and chromosome assignment of the murine p36 calpactin I heavy chain gene

Abstract: p36 is a major substrate of both viral and growth factor receptor associated protein kinases. This protein has recently been named calpactin I heavy chain since it is the large subunit of a Ca2(+)-dependent phospholipid and actin binding heterotetramer. The primary structure of p36 has been determined from analysis of cloned cDNA. The protein contains 338 amino acids, has an approximate molecular weight of 39,000, and is comprised of several distinct domains, including four 75 amino acid repeats. From two over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 59 publications
0
11
1
Order By: Relevance
“…Amiguet et al [28] have described the 22-exon structure for the AIIM gene. They observed that the intron locations do not correspond with the boundaries between the annexin repeats, although the 4/5 (position 19/20 AIIM2) and 10/11 (AIIM4) exon boundaries occur at equivalent positions within repeats 2 and 4 respectively.…”
Section: Location Ojintronsmentioning
confidence: 99%
“…Amiguet et al [28] have described the 22-exon structure for the AIIM gene. They observed that the intron locations do not correspond with the boundaries between the annexin repeats, although the 4/5 (position 19/20 AIIM2) and 10/11 (AIIM4) exon boundaries occur at equivalent positions within repeats 2 and 4 respectively.…”
Section: Location Ojintronsmentioning
confidence: 99%
“…2 of which 10 out of 26 have split codons. The frequency of split codons in other annexin genes is similar, typically 4 of 12 (15)(16)(17)(18)(19)(20). The first coding exon is 43 bp long, smaller than the corresponding exons of the annexin I and I genes, and consistent with the fact that the N-terminal sequence prior to the first protein repeat is smaller in annexin VI than in either annexins I or II.…”
Section: Resultsmentioning
confidence: 99%
“…The first coding exon is 43 bp long, smaller than the corresponding exons of the annexin I and I genes, and consistent with the fact that the N-terminal sequence prior to the first protein repeat is smaller in annexin VI than in either annexins I or II. The sizes of the remaining coding exons are identical to those of the corresponding exons of the annexin I and II genes (15)(16)(17)(18)(19)(20). The exceptions to this are exon 21 that is only 18 nt and is alternatively spliced (2) and exon 26 that is 406 bp and includes the translation stop codon and 3' untranslated sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations